2018
DOI: 10.1017/s1751731118001301
|View full text |Cite
|
Sign up to set email alerts
|

Review: Adaptation of ruminant livestock production systems to climate changes

Abstract: There is growing evidence on the extent to which projected changes in climate, including increases in atmospheric levels of carbon dioxide, higher temperatures, changes in amount, seasonality and variability of precipitation and increases in extreme weather events, may affect future availability of ruminant animal products. Elements of climate change affect livestock systems through direct impacts on animal physiology, behaviour, production and welfare and indirectly through feed availability, composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 56 publications
3
69
1
10
Order By: Relevance
“…reduced consumption of animal products) or decrease GHG emissions per animal. Furthermore, intensification can lead to greater vulnerability under a changing climate (Henry et al, 2018). Thus, improving individual animal productivity as a GHG mitigation approach will likely be insufficient if not accompanied by measures to decrease CH 4 emissions per animal.…”
Section: Reducing Net Emissions V Emissions Intensitymentioning
confidence: 99%
“…reduced consumption of animal products) or decrease GHG emissions per animal. Furthermore, intensification can lead to greater vulnerability under a changing climate (Henry et al, 2018). Thus, improving individual animal productivity as a GHG mitigation approach will likely be insufficient if not accompanied by measures to decrease CH 4 emissions per animal.…”
Section: Reducing Net Emissions V Emissions Intensitymentioning
confidence: 99%
“…Therefore, future selection should aim for a balance between heat adaptation, health and production. Henry et al [101] suggested an alternative approach to incorporate specific thermotolerant genes into high performing breeds while avoiding undesirable genotypic traits. Incorporation of specific genes to improve thermotolerance requires identifying/mapping of individual genes responsible for better adaptive traits and this approach opens the way towards an improved breeding program through marker-assisted selection and transgenics.…”
Section: The Potential For Genetic Improvement To Improve Resilience mentioning
confidence: 99%
“…Dado que las diferencias en la producción de pasto no son de magnitud entre los períodos analizados, ni la producción de carne ni el margen bruto muestran diferencias significativas entre períodos Los resultados presentados muestran que las condiciones para la producción de pasto tienden a mejorar levemente en los períodos futuros dadas las mayores temperaturas y los incrementos moderados en las precipitaciones promedio. Sin embargo, una mayor variabilidad de las precipitaciones en los períodos futuros limitarían incrementos mayores en la producción de pasto, carne y en el margen bruto logrado (Thornton et al, 2009;Henry et al, 2018). Estas condiciones hacen que en el Futuro Lejano podría mantenerse una mayor carga animal, engordando todos los animales producidos en un mayor número de años que en los otros períodos.…”
Section: Histórico Futuro Cercano Futuro Lejanounclassified